Retrieval of Overextruded Separated Instrument: An Approach with Ultrasonics - Budhathoki, Ashmita; Joshi, Neera; Prajapati, Kranti (Journal of College of Medical Sciences-Nepal, 2024)
Background Instrument separation is a frequent procedural mishap that occurs with rotary instruments than hand instruments. Separated instrument beyond apical foramen is a major threat as it greatly influences the treatment outcome and leaves psychosocial impact on patient. Retrieval of overextruded instrument is necessary and can be done via both surgical and non-surgical approach. A conservative non-surgical approach is attempted first. Use of Ultrasonics in retrieval of separated instrument can be done effectively and safely. This is a case report of an 18 years old girl who was referred for retrieval of a separated instrument. The concern was in her upper central incisors which is an esthetically dominant focal point in dental composition. Non-surgical retrieval was planned with the use of ultrasonics and enhanced magnification. The case was successfully managed with retrieval of separated instrument and root canal obturation done in same visit. The patient was asymptomatic in one year follow up. Ultrasonics are simple and less invasive approach to be used for separated instrument retrieval. However, proper use of rotary instruments should always be encouraged to minimise the mishap.